2013
DOI: 10.1002/ar.22727
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Microscopic Colitis of Rhesus Macaques: Quantitative Assessment of Colonic Mucosa

Abstract: Idiopathic chronic diarrhea (ICD) is a common cause of morbidity and mortality among juvenile rhesus macaques. While lesions may be absent at colonoscopy, the histopathologic evaluation of the biopsy specimens is consistent with human macroscopic colitis (MC). In this study, we developed an isotropic uniform random sampling method to evaluate macroscopic and microscopic changes and applied it on proximal ascending colon in monkeys. Colonic tissue and peripheral blood specimens were collected from six MC and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 68 publications
4
42
1
Order By: Relevance
“…Evaluation of H&E stained sections revealed variable amounts of inflammation in animals of both groups (Supplementary Table 4), consistent with previous findings in captive rhesus monkeys [31]. In the control group, two animals had histopathologically normal proximal colon tissue, one had moderate proliferation of Peyer’s patches and two displayed mild to moderate colitis.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Evaluation of H&E stained sections revealed variable amounts of inflammation in animals of both groups (Supplementary Table 4), consistent with previous findings in captive rhesus monkeys [31]. In the control group, two animals had histopathologically normal proximal colon tissue, one had moderate proliferation of Peyer’s patches and two displayed mild to moderate colitis.…”
Section: Resultssupporting
confidence: 88%
“…The presence of inflammatory cell infiltration or colitis found in varying degrees in animals of both groups may have affected the detection of 6-OHDA-induced inflammation. Colitis occurs in about 20% of monkeys in captive rhesus colonies [31]; therefore it is unsurprising that at least one animal in the 6-OHDA-treated and control groups had mild to moderate colitis. Another possibility is that a difference in inflammation and oxidative stress may not have been observed due to the length of time post-intoxication (3 months); it should be mentioned that the monkeys in this study did not have upregulation of inflammatory markers in the heart three months after 6-OHDA administration, despite extensive left ventricle catecholaminergic loss [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In studies with unrelated, chronic bacterial colitis-affected macaques, an overgrowth of Pasteurellaceae and Enterobacteriaceae , as well as decreased microbial diversity was observed. Taken together, our findings also corroborate that gluten sensitivity can contribute to chronic bacterial enterocolitis e.g., one of the major health concerns of polyfactorial origin in captive macaques [24,44,71,72]. …”
Section: Discussionsupporting
confidence: 83%
“…More recently, at the California National Primate Research Center (CNPRC) diarrhea accounted for 50% of the veterinary caseload [Elmore et al, ]. Present estimates reveal that 44% of non‐research related mortality at the CNPRC was associated with diarrhea or colitis upon necropsy, and, according to Ardeshir et al [], 25% of these cases are diagnosed as chronic with a 5% annual incidence. Meanwhile, between 15% and 40% of rhesus macaques housed at the Oregon National Primate Research Center (ONPRC), are reported to have experienced diarrheal illness that requires veterinary treatment for dehydration, electrolyte imbalance, or weight loss; between 20% and 30% of these animals either succumb to the disease or are culled [Prongay et al, ].…”
Section: Introductionmentioning
confidence: 96%
“…A more recent report by Ardeshir et al [] claimed that measurements of peripheral blood cytokines, chemokines and growth factors can be used for predicting if a rhesus macaque would develop CDD. Although variation in colonic volume and surface area between animals euthanized for diarrhea and for other reasons can only be determined posthumously, such anatomical differences can be used for retrospectively identifying probands and their living relatives [Ardeshir et al, ].…”
Section: Introductionmentioning
confidence: 99%